Sesquiterpene production in methyl jasmonate-induced Persicaria minor cell suspension culture - Piriyatasni Sellapan,; Emelda Rosseleena Rohani,; Normah Mohd Noor, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Sesquiterpenes are a three-isoprene unit compounds which belong to terpenoid family of secondary metabolites. These volatile compounds are one of the major constituents of essential oils in plants and plays major roles in plant signaling of defense mechanism. The effects of methyl jasmonate (MeJA) concentrations (100 and 200 μM) on the production of sesquiterpene compounds after incubation period for 1, 3, and 6 days were investigated in Persicaria minor cell suspension culture. Headspace Solid-Phase Microextraction (HS-SPME) method was used to absorb volatile compounds from suspension cells and liquid medium. They were then analyzed through Gas Chromatography-Mass Spectrometry (GC-MS) to identify sesquiterpene compounds. Among the 15 sesquiterpene compounds identified, α- muurolene was found in significantly higher concentration in all MeJA treated cultures. The results showed that α-muurolene was detected in the suspension cells at the highest peak area of 14.17% at 100 μM MeJA treated cultures with 3-day incubation. Analysis of liquid medium of the treatments identified secretion of α-muurolene into the culture medium, with total peak area of 0.72%. These results showed that sesquiterpene production in MeJA induced P. minor suspension culture depended on the MeJA concentration and also culture incubation period.